2011
DOI: 10.1186/1752-1947-5-136
|View full text |Cite
|
Sign up to set email alerts
|

A giant adrenal lipoma presenting in a woman with chronic mild postprandial abdominal pain: a case report

Abstract: IntroductionAdrenal lipomas are rare, small, benign, non-functioning tumors, which must be histopathologically differentiated from other tumors such as myelolipomas or liposarcomas. They are usually identified incidentally during autopsy, imaging, or laparotomy. Occasionally, they may present acutely due to complications such as abdominal pain from retroperitoneal bleeding, or systemic symptoms of infection. We report a giant adrenal lipoma (to the best of our knowledge, the second largest in the literature) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 11 publications
(41 reference statements)
1
11
0
Order By: Relevance
“…Chronic inflammatory cells (Kapetanakis et al 2011) were found in a case having symptoms for 10 years. Also, a case had active inflammation and abscess as a result of adjacent infection as a result of percutaneous nephrolithotomy (Gupta et al 2009).…”
Section: :3mentioning
confidence: 88%
See 2 more Smart Citations
“…Chronic inflammatory cells (Kapetanakis et al 2011) were found in a case having symptoms for 10 years. Also, a case had active inflammation and abscess as a result of adjacent infection as a result of percutaneous nephrolithotomy (Gupta et al 2009).…”
Section: :3mentioning
confidence: 88%
“…There are 24 well-documented cases of adrenal lipomas in the English literature (Table 2) (Lange 1966, Prinz et al 1982, Avinoach et al 1989, Lam et al 1997, Ghavamian et al 1998, Sharma et al 1998, Büttner 1999, Lam & Lo 2001, Milathianakis et al 2002, Rodríguez-Calvo et al 2007, Shumaker et al 2008, Gupta et al 2009, Shah & Bhatti 2009, Singaporewalla et al 2009, Goldenberg et al 2011, Gunay et al 2011, Kapetanakis et al 2011, Patel et al 2011, Jain et al 2012, Zhao et al 2014. The first case in the English literature was reported by Lange in 1966(Lange 1966).…”
Section: Adrenal Lipomamentioning
confidence: 99%
See 1 more Smart Citation
“…However, with widespread use of imaging techniques more such asymptomatic masses have been discovered, recently (3,13). Uncommonly, patients show symptoms such as abdominal pain, biliary colic, lumbar pain or nephropathy and hypertension (12)(13)(14). Our patient suffered from abdominal pain, too.…”
Section: Discussionmentioning
confidence: 76%
“…Adrenal lipoma is a very rare nonfunctional tumor with unknown pathogenesis (12). However, with widespread use of imaging techniques more such asymptomatic masses have been discovered, recently (3,13).…”
Section: Discussionmentioning
confidence: 99%